Synthesis and cytotoxic evaluation of novel chromenes and chromene(2,3-d)pyrimidines - Mahmoud N. M. Yousif, Abdel-Rahman B. A. El-Gazzar, Ahmed A. Fayed, May A. El-Manawaty, Nabil M. Yousif (Journal of Applied Pharmaceutical Science, 2020)
The synthesis of novel compounds starting from 2-amino-8-(2-chlorobenzylidene)-4-(2-chlorophenyl)-5,6,7,8- tetrahydro-4H-chromene-3-carbonitrile 2 has been studied. Diarylidene cyclohexanone reacts with malononitrile to afford compound 2. Compound 2 reacts with benzoyl chloride to afford compound 3. N-(8-(2-chlorobenzylidene)- 4-(2-chlorophenyl)-3-cyano-5,6,7,8-tetrahydro-4H-chromen-2-yl)benzamide 3 reacts with acetic anhydride to afford compound 4. Compound 2 reacts with acetic anhydride to afford 9-(2-chlorobenzylidene)-5-(2-chlorophenyl)-2- methyl-3,5,6,7,8,9-hexahydro-4H-chromeno[2,3-d]pyrimidin-4-one 5. Chromene derivative 2 reacts with formic acid to give compound 6. Compounds 4–6 react with phosphorus oxychloride to give compounds 7a–c. Chromeno[2,3-d] pyrimidine derivatives 7a–c react with hydrazine hydrate to afford compounds 8a–c. Chromeno[2,3-d]pyrimidine derivatives 8a,b react with xylose and glucose to give compounds 9a–d. Chromeno[2,3-d]pyrimidine derivatives 9a–d react with acetic anhydride to give compounds 10a–d. Screening of most of the synthesized compounds against A-549, CaCo-2, and HT-29 cell lines were done. 2-Amino-8-(2-chlorobenzylidene)-4-(2-chlorophenyl)-5,6,7,8- tetrahydro-4H-chromene-3-carbonitrile 2 gives high cytotoxic activity against A-549 and HT-29 cancer cell lines as compared to doxorubicin as the reference drug.
Keywords: Tetrahydrochromenes, chromene(2,3-d)pyrimidines, chromenotriazolopyrimidine, pyrimidines, triazolopyrimidine, cytotoxic activity.